PENGARUH BRAND TRUST, PERCEIVED VALUE, DAN CUSTOMER SATISFACTION TERHADAP BRAND LOYALTY PADA PELANGGAN KLINIK KECANTIKAN NATASHA SKIN CARE DI KOTA SURABAYA - Saldy, Zhaskia (Kajian Ilmiah Mahasiswa Manajemen, 2013)
In today’s world, the competition amongbeauty clinics is becoming more intense. As a result, the need and the desire of the consumers must be considered by companies. This objective of this study is toinvestigate the effect ofbrand truston brand loyaltyinbeauty clinic NatashaSkinCareinSurabaya. In specific, the study also determine the influence of perceived value on brand loyalty and the influence of customer satisfaction on brand loyalty for the clinic’s customer.This study examines 150 respondents, who are the clinic’s customer. The type of analysis being used in this study is multiplelinear regressionanalysis. The results indicated thatbrand trust affects brandloyalty in a positive manner,perceived value has a positive effect on brand loyalty and customer satisfaction also has a positive effect on brand loyalty.To sum up, by knowing the effect of brandtrust, perceived value, customer satisfaction and brand loyalty, it can help companies to improve the profitability of customerswhichultimately establih the customer loyalty.